2020
DOI: 10.1186/s40468-020-00112-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a rating scale for Iranian EFL academic writing assessment: a mixed-methods study

Abstract: The present study reports the process of development and validation of a rating scale in the Iranian EFL academic writing assessment context. To achieve this goal, the study was conducted in three distinct phases. Early in the study, the researcher interviewed a number of raters in different universities. Next, a questionnaire was developed based on the results of the interview along with the related literature. Later, the questionnaire was sent to thirty experienced raters from ten major state universities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…According to them, in order to enhance Iranian EFL teachers' competence and preparation for writing assessment, there is a great need for significant improvement in EFL teacher education programs and recruitment. As an example of poor writing assessment literacy among Iranian EFL writing teachers, Ghanbari and Barati (2020) found that there was no objective rating scale in use among the raters in the Iranian EFL academic writing assessment. Based on this, they suggested that higher educational planning bodies in the context should consider the design and implementation of rater training courses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to them, in order to enhance Iranian EFL teachers' competence and preparation for writing assessment, there is a great need for significant improvement in EFL teacher education programs and recruitment. As an example of poor writing assessment literacy among Iranian EFL writing teachers, Ghanbari and Barati (2020) found that there was no objective rating scale in use among the raters in the Iranian EFL academic writing assessment. Based on this, they suggested that higher educational planning bodies in the context should consider the design and implementation of rater training courses.…”
Section: Discussionmentioning
confidence: 99%
“…This was mostly due to the missing place of a special training program for writing teachers. Similarly, studies in different contexts (Alkharusi et al, 2012;Ghanbari & Barati, 2020;Jannati, 2015;Tayyebi & Moradi Abbasabadi, 2020;Taylor, 2009;Valizadeh, 2019) have revealed that many writing teachers receive little or no formal assessment training in the preparatory programs and often they do not have enough knowledge about assessment. Similar to the findings of the present study, the literature shows that in different EFL/ESL writing assessment contexts, the pre-service and in-service teachers are not provided with a holistic and experiential training program that enables them to integrate the theoretical knowledge of the teachers with the realities of their practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome of the writing assessment derives from an interaction among many elements of assessment including rater, test taker, scale, scoring, and practice. Therefore, the quality of rating has a significant bearing for the interpretation of outcomes (Ghanbari & Barati, 2020 ; Hamp-Lyons, 2007 ), and hence, different interactions regarding all these aspects of assessment can lead to different outcomes. In writing assessment, the impact of rating scale on the rating process (Barkaoui, 2010b ), complexity of rating criteria (Joe et al, 2011 ), and raters’ perception can induce the lowest inter-rater reliability.…”
Section: Introductionmentioning
confidence: 99%